The Influence of the Project Based Learning (PjBL) Model on Student Learning Outcomes in Solar System Material Class VI SD Negeri 22 Banda Aceh - Syari, Nur Ayuni; Fitriani, Suci; vitoria, linda (Universitas Syiah Kuala, 2024)
This study aims to determine the effect of the Project Based Learning (PjBL) model on student learning outcomes in the solar system material for class VI SD Negeri 22 Banda Aceh. This research approach is a quantitative approach. This type of research is an experiment with a true experimental design. The population in this study were all students of class VI SD Negeri 22 Banda Aceh with a sample of students in class VI B and VI C. Data collection used tests in the form of pretest and posttest. Data analysis techniques using the N-gain test and independent t-test. The results showed that the significance (2 tailed) was 0.000. Where 0.000 0.05 so that there is an influence of the Project Based Learning (PjBL) model on student learning outcomes in the solar system material for class VI SD Negeri 22 Banda Aceh.